PENINGKATAN HYGIENITAS INDUSTRI TAHU MELALUI PERBAIKAN SISTEM PEMASAKAN DAN LINGKUNGAN KERJA - Murni Murni; Sri Utami Handayani; Hermawan Dwi Ariyanto; Sutrisno Sutrisno; Didik Ariwibowo (Sekolah Vokasi Universitas Diponegoro, 2021)
Tofu is one of the traditional Indonesian foods that are cheap and have high nutritional value. Consumption of tofu reaches more than 1.5 ounces/capita per week, and the trend continues to increase. Tofu production is generally carried out by Micro, Small and Medium Enterprises (MSMEs), including Berkah Jaya and Sumber Hidup in Ungaran. In these SMEs the production of tofu is still not hygienic, for example a container made of cement. The tofu rack is also not sufficient so that the tofu container is often placed on the floor. This activity aims to increase the productivity and hygiene of the tofu industry through replacing the barrel material from cement to stainless steel and making tofu container racks.